2018
DOI: 10.1111/and.12981
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and rutin ameliorates sulphasalazine‐induced spermiotoxicity, alterations in reproductive hormones and steroidogenic enzyme imbalance in rats

Abstract: Certain dietary flavonoids exhibit protective potentials against drug-induced male reproductive toxicities. We investigated the protective effects of quercetin and rutin on sulphasalazine-induced alterations in steroidogenic enzyme activity, hormone profile and spermiotoxicity in rats. Sulphasalazine (SASP, 600 mg/kg bw) was administered alone or in combination with quercetin (20 mg/kg bw) or rutin (10 mg/kg bw) for 14 days. SASP treatment significantly increased relative weights of the epididymis and seminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 57 publications
6
29
0
Order By: Relevance
“…An improvement in testicular architecture of Que-BR rabbits under HS might be due to antioxidant property of quercetin. The current findings were supported by earlier reports where protective effects of quercetin against histological damage induced by different toxic agents were observed (Sonmez et al, 2014;Altintas et al, 2015;Khorsandi et al, 2017;Osawe and Farombi, 2018;Badr et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…An improvement in testicular architecture of Que-BR rabbits under HS might be due to antioxidant property of quercetin. The current findings were supported by earlier reports where protective effects of quercetin against histological damage induced by different toxic agents were observed (Sonmez et al, 2014;Altintas et al, 2015;Khorsandi et al, 2017;Osawe and Farombi, 2018;Badr et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…21 In another study, GST levels significantly increased with the use of rutin. 22 Both results were replicated in our experiment.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, adult male albino rats with atrazine-induced reproductive toxicity administered quercetin at 10 mg −1 kg −1 of body weight for 21 days had higher levels of testosterone compared with the control [49]. Furthermore, quercetin at 20 mg −1 kg −1 of body weight for two weeks restored plasma testosterone induced by sulphasalazine in male rats [50]. Recently, it has been shown that quercetin at 20 mg −1 kg −1 of body weight for 28 days is able to attenuate testosterone depletion induced by cadmium chloride in male Wistar rats [51].…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Recently, it has been shown that quercetin at 20 mg −1 kg −1 of body weight for 28 days is able to attenuate testosterone depletion induced by cadmium chloride in male Wistar rats [51]. Such protective effects may be attributable to the antioxidant activity of quercetin as it was found to increase the activity of testicular antioxidants (superoxide dismutase, glutathione reductase, and catalase) and significantly reduce the level of malondialdehyde in testicular tissue [47,50,52].…”
Section: Mechanistic Studiesmentioning
confidence: 99%